Emerging Technologies in Hazardous Waste Management 8 - Tedder, D. William.; Pohland, Frederick G. (Springer US, 2002)
Several long-term trends in technology evolution have become apparent since these symposia began in 1989. Earlier presenters more frequently discussed treatment methods involving harsh and extensive human intervention. As the symposia have continued, the number of presentations describing extremely harsh and expensive treatment technologies have gradually been supplanted by more subtle and gentler methods. Such methods include subsurface-engineered barriers, phytoremediation, and bioremediation. Nineteen manuscripts were selected for inclusion in this volume, based upon peer review, scientific merit, the editors' perceptions of lasting value or innovative features, and the general applicability of either the technology itself or the scientific methods and scholarly details provided by the authors. General topics include: soil treatment, groundwater treatment, and radioactive waste treatment.